Decision-making cognition in mania and depression. - Murphy, F; Rubinsztein, J; Michael, A; Rogers, R; Robbins, T; Paykel, E; Sahakian, B (2001)
BACKGROUND: Despite markedly different clinical presentations, few studies have reported differences in neuropsychological functioning between mania and depression. Recent work has suggested that differences may emerge on cognitive tasks requiring affective processing, such as decision-making. The present study sought to compare decision-making cognition in mania and depression in order to clarify the current profiles of impairment for these disorders and to contribute to our more general understanding of the relationship between mood and cognition. METHODS: Medicated manic patients, depressed patients, and normal healthy controls completed a computerized decision-making task. All subjects were asked to win as many points as possible by choosing outcomes based on variably-weighted probabilities and by placing 'bets' on each decision. RESULTS: Both patient groups were impaired on this task, as evidenced by slower deliberation times, a failure to accumulate as many points as controls and suboptimal betting strategies. Manic, but not depressed, patients made suboptimal decisions--an impairment that correlated with the severity of their illness. CONCLUSIONS: These findings are consistent with a growing consensus that manic and depressed patients are characterized by significant impairments in cognitive and particularly executive, functioning. Furthermore, the distinct patterns of observed impairment in manic and depressed patients suggests that the nature and extent of cognitive impairment differ between these two groups. Viewed in the context of other recent studies, these findings are consistent with a role for the ventromedial prefrontal cortex in mediating mood-cognition relationships.